Activated ERK/FOXM1 Pathway by Low‐Power Laser Irradiation Inhibits UVB‐Induced Senescence Through Down‐Regulating p21 Expression. Issue 1 (23rd September 2013) - Ling, Qingzhou; Meng, Chengbo; Chen, Qun; Xing, Da
Abstract Cellular senescence is a growth‐arrest program that limits cell proliferation. Low‐power laser irradiation (LPLI) has been demonstrated to promote cell proliferation. However, whether LPLI can inhibit cellular senescence remains unknown. In the present study, to investigate the functional role of LPLI against skin aging, we used ultraviolet radiation b (UVB) to induce cell senescence. We first report that LPLI can delay UVB‐induced cell senescence. The senescence‐associated β‐galactosidase (SA‐β‐Gal) activity and p21 expression, hallmarks of senescent cells, were decreased in the Forkhead box transcription factor FOXM1‐dependent manner under treatment with LPLI. The effect of LPLI was further enhanced with an overexpression of FOXM1, and abolished when FOXM1 was knockdown with short hairpin RNA (shRNA). Furthermore, LPLI activated the extracellular regulated protein kinases (ERK) that was upstream of FOXM1. This led to FOXM1 phosphorylation and nuclear translocation. Nuclear translocation enhanced FOXM1 transcriptional activity and promoted its downstream target gene c‐Myc expression that could inhibit p21 expression. These findings highlight the protective effects of ERK/FOXM1 pathway against UVB‐induced cell senescence, suggesting a potential protecting strategy for treating skin aging by LPLI. J. Cell. Physiol. 229: 108–116, 2014. © 2013 Wiley Periodicals, Inc.